FY 2019 South Africa Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2020)
The Country Opinion Survey in South Africa assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in South Africa perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in South Africa on 1) their views regarding the general environment in South Africa; 2) their overall attitudes toward the WBG in South Africa; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in South Africa; and 4) their perceptions of the WBG’s future role in South Africa.